Interference with spectrophotometric analysis of nucleic acids and proteins by leaching of chemicals from plastic tubes. (April 2010) - Lewis, L. Kevin; Robson, Michael H.; Vecherkina, Yelena; Ji, Chang; Beall, Gary W.
Absorbance spectroscopy is routinely used to monitor the concentrations of nucleic acids and proteins within solutions and to assess changes in their structure caused by interaction with chemicals or other biomolecules. Biological samples used for such analyses are manipulated and stored in small microcentrifuge tubes (microtubes) composed of polypropylene plus several plastic additives. Here we demonstrate that normal handling of laboratory microtubes causes leaching of light-absorbing chemicals into biological samples that interfere with spectrophotometric measurements. The leached chromophores absorbed UV light strongly at 220 and 260 nm, which are the wavelengths normally used to detect and quantitate proteins and DNA. Some common laboratory techniques, including sonication and PCR, were particularly effective inducers of leaching. The magnitude of the increase in absorbance was dependent upon both exposure time and heat history, with greatest induction after tubes were warmed to temperatures at or above 37°C. Mass spectrometry revealed that aqueous solutions stored in plastic microtubes accumulate a complex mixture of leached chemicals with molecular masses of 200–1400 Da. Leaching was ubiquitous among commercially available brands of microtubes, indicating a persistent source of error in biomolecule detection and concentration measurements.